1981
DOI: 10.1073/pnas.78.2.702
|View full text |Cite
|
Sign up to set email alerts
|

Visible absorption spectrum of liquid ethylene

Abstract: The visible pbsorption spectrum of liquid ethylene at -108 K from 5500 A to 7200 A was measured by using a pulsed tunable dye laser, immersed-transducer, gated-detection opto-acoustic spectroscopy technique. The absorption features show the strongest band with an absorption coefficient of m2 x 10-2 cm-' and the weakest band with an absorption coefficient of _I x 10-4 cM-. Proposed assignments of the observed absorption peaks involve combinations of overtones of local and normal modes of vibration of ethylene.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The main contributions to high vibrational overtone studies in cryogenic liquids have been made by Patel et al and Manzanares et al Patel et al used photoacoustic detection for the first time to measure high energy overtones (Δυ = 4−6) of condensed methane, ethylene, and solid para -hydrogen. , Even though only pure samples were studied, Patel et al showed the suitability of photoacoustic methods to measure overtones at low temperatures. Similarly, Manzanares et al applied photoacoustic spectroscopy to cryogenic samples; however, they also prepared solutions in condensed argon.…”
Section: Introductionmentioning
confidence: 99%
“…The main contributions to high vibrational overtone studies in cryogenic liquids have been made by Patel et al and Manzanares et al Patel et al used photoacoustic detection for the first time to measure high energy overtones (Δυ = 4−6) of condensed methane, ethylene, and solid para -hydrogen. , Even though only pure samples were studied, Patel et al showed the suitability of photoacoustic methods to measure overtones at low temperatures. Similarly, Manzanares et al applied photoacoustic spectroscopy to cryogenic samples; however, they also prepared solutions in condensed argon.…”
Section: Introductionmentioning
confidence: 99%
“…Although students are provided with some basic guidance, they independently figure out the signature patterns of IR spectra within a functional group and later deduce how to distinguish between functional groups containing similar structural features. Manipulatives have been used successfully in organic laboratory; for example, Nelson created a two-page summary device to help students distinguish trends in electrophilic aromatic substitution (22) as well as a two-page device called the Nucleophile/Electrophile Reaction Guide to help students visualize reactions (23). We could find only one example of a manipulative for an instrumental technique, which was a general chemistry experiment for exposing students to fragmentation patterns in GC-MS (24).…”
mentioning
confidence: 99%
“…They recorded overtone (Δυ = 5−7) absorptions of C−H and O−H bonds in a variety of samples at room temperature. Recently, Manzanares reported the application of thermal lens spectroscopy to cryogenic samples, measuring the C−H (Δυ = 6) overtone transition of liquid methane and methane−argon solutions. Previously, photoacoustic spectroscopy had been used to study these transitions in liquid methane , and ethylene . Because thermal lensing allows analysis of dilute solutions, the advantages of liquefied rare gases as solvents can be fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, photoacoustic spectroscopy had been used to study these transitions in liquid methane 16,17 and ethylene. 18 Because thermal lensing allows analysis of dilute solutions, the advantages of liquefied rare gases as solvents can be fully exploited. High transparency in a broad spectral range, minimal perturbations of degrees of freedom, and optical homogeneity are always desirable solvent qualities in vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%